Royalty Payments for Music Play in Cafes and Restaurants: Impact on The Right to Freedom of Communication and MSME Revenues - Muslim, Shohib; Syuhada, Esa Arung; Utama, Satria Putra; Paulina, Julinta; Wuryanta, Aloysius Gonzage Eka Wenats (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The explanation above indicates that this research is a qualitative study with a descriptive approach, namely an approach that aims to describe each of the main topics used in this article. The researcher will describe the implementation of royalty payments by MSMEs and its impact on MSME income, the implementation of the royalty payment system that has not been optimally absorbed from the perspective of songwriters, and clarity on who pays royalties, whether the singer or the event organizer. The data used in this article is secondary data obtained by the researcher from credible sources such as scientific articles, websites, books, and so on. This data is analyzed through the stages of data collection, data reduction, data selection, and drawing conclusions. The Conclusion in this article show that this can affect MSMEs that do not have a good MSME and do not include royalty payments in routine expenses. Conversely, this does not affect MSMEs that have included royalty payments in routine expenses. Regarding the right to freedom of communication, the researcher believes that this right can be limited if other community rights are violated. Furthermore, it has been confirmed that royalty payments are not optimal and will be improved as soon as possible by the government. The government has also emphasized that the party responsible for paying royalties is the event organizer, not the singer.